Critical evaluation of the role of the Toll-like receptor 18-Wheeler in the host defense of Drosophila. - Ligoxygakis, P; Bulet, P; Reichhart, J (2002)
Essential aspects of innate immune responses to microbial infections appear to be conserved between insects and mammals. In particular, in both groups, transmembrane receptors of the Toll superfamily play a crucial role in activating immune defenses. The Drosophila Toll family member 18-Wheeler had been proposed to sense Gram-negative infection and direct selective expression of peptides active against Gram-negative bacteria. Here we re-examine the role of 18-Wheeler and show that in adults it is dispensable for immune responses. In larvae, 18wheeler is required for normal fat body development, and in mutant larvae induction of all antimicrobial peptide genes, and not only of those directed against Gram-negative bacteria, is compromised. 18-Wheeler does not qualify as a pattern recognition receptor of Gram-negative bacteria.